Strategi Pemberdayaan Desa Adat dengan Pembentukan Forum Komunikasi antar Desa Adat - Kartika, Ni Gusti Ayu (Institut Hindu Dharma Denpasar, 2019)
Traditional village is a traditional institution that serves as a forum for the villagers to perform various spiritual, cultural, social and economic, in order to achieve tranquility and prosperity of life born inner. The indigenous village autonomy manifests itself in the administration of the government, which can apply in and out, and shoulder to shoulder with the village office in carrying out the development. In this era of globalization, indigenous villages experience internal and external challenges that may interfere with their sustainability. With the establishment of communication forums between custom villages, it is expected that traditional villages will exist, resilient and empowered in facing these challenges.